History Versus Expectations: A Comment - Fukao, K.; Benabou, R. (Quarterly Journal of Economics, 1993)
Kyoji Fukao, Roland Benabou; History Versus Expectations: A Comment, The Quarterly Journal of Economics, Volume 108, Issue 2, 1 May 1993, Pages 535–542, ht